Possibilities of lipid clinics in identifying patients with familial hypercholesterolemia - Z. F. Kim; A. S. Galyavich; D. I. Sadykova; L. M. Nurieva (Российский кардиологический журнал, 2023)
Aim. To assess the detection rate of familial hypercholesterolemia among outpatients visiting a lipidologist.Material and methods. We analyzed the causes and nature of lipid metabolism disorders in patients of the Adult Lipidology Center as follows: 1233 people aged 18-84, including 777 women (63,02%) and 456 men (36,98%). Biomaterial samples from 421 patients with the phenotype of definite, possible or probable familial hypercholesterolemia were studied by massive parallel sequencing using a panel of 5 genes associated with familial hypercholesterolemia (LDLR, LDLRAP1, APOB, APOE, PCSK9). For statistical processing, descriptive statistics methods were used.Results. Working-age patients apply 1,56 times more often than patients of the older age group (60,91% vs 39,09%), and the vast majority of them were referred by a primary care physician based on data from periodic health examinations. The mean level of total cholesterol and low-density lipoprotein cholesterol in the lipidology center was 7,58 and 4,8, respectively. Out of 421 samples, 127 patients (10,3% of the total number of patients and 30,16% of the number of biosamples) had previously described variants of the LDLR, APOB and/or PCSK9 genes associated with familial hypercholesterolemia.Conclusion. The detection rate of definite familial hypercholesterolemia ranges from 5,51 to 8,43% of outpatients visiting a lipidologist, while the proportion of verified carriers of gene mutations related to familial hypercholesterolemia is 10,3%. The diagnosis should not be rejected with a formally low probability according to the S. Broom and DLCN criteria, as well as when identifying data suggestive of secondary lipid metabolism disorders.